2006
DOI: 10.1002/pola.21668
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel hyperbranched polybenzimidazoles based on an AB2 monomer containing four amino groups and one carboxylic group

Abstract: A new kind of AB2 monomer, 4‐[2,6‐bis(3,4‐diaminophenyl)pyridin‐4‐yl]benzoic acid, was synthesized, and several hyperbranched polybenzimidazoles (HPBIs) were prepared through self‐polymerization followed by modification reactions with end‐capping reagents such as 4‐methyl benzoic acid and 3‐[3,5‐bis(trifluoromethyl)phenoxy] benzoic acid. The HPBIs had good solubility in strongly aprotic solvents, such as N‐methyl‐2‐pyrrolidone, N,N′‐dimethylformamide, N,N′‐dimethylacetamide, and dimethyl sulfoxide. They also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The same group has also reported that the commercial PBI could be crosslinked with another kind of crosslinker, dichloromethylphosphonic acid, and the relevant crosslinked membranes displayed significantly higher tensile strength than the linear PBI at similar doping levels 19. We have previously reported that crosslinked hyperbranched PBI membranes could maintain reasonably high‐mechanical strength at high PA‐doping levels, which is superior to the commercial PBI membranes 20, 21, 35…”
Section: Introductionmentioning
confidence: 92%
“…The same group has also reported that the commercial PBI could be crosslinked with another kind of crosslinker, dichloromethylphosphonic acid, and the relevant crosslinked membranes displayed significantly higher tensile strength than the linear PBI at similar doping levels 19. We have previously reported that crosslinked hyperbranched PBI membranes could maintain reasonably high‐mechanical strength at high PA‐doping levels, which is superior to the commercial PBI membranes 20, 21, 35…”
Section: Introductionmentioning
confidence: 92%
“…PBI is used for various purposes, especially high‐temperature applications, fiber spinning, reverse osmosis membranes, and fluorescence sensors for halide ions 16, 31. A variety of PBI polymers have been synthesized and reported in the literature, such as poly[2,2′‐( m ‐phenylene)‐5,5′‐benzimidazole] (m‐PBI), poly(2,5‐benzimidazole),32 pyridine‐based PBI,11 sulfonated PBI,22 hyperbranched PBI,33 fluorinated PBI,18 and naphthalene‐based PBI 34…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor solubility of PBIs, a result of their highly rigid backbones, is a major barrier to their practical use. Many efforts have been made to improve the solubility and processability of these materials by modifying their polymer structures while preserving their desirable properties . The introduction of amide groups along the polymer backbone has been found to improve solubility by disrupting the rigid structure of the polymer without sacrificing its thermal or mechanical properties to any great extent , .…”
Section: Introductionmentioning
confidence: 99%